The Evolution Of The University Textbook For Teaching Functional Writing Skills In Saudi Universities/ ØªØ·ÙˆØ± Ø§Ù„ÙƒØªØ§Ø¨ Ø§Ù„Ø¬Ø§Ù…Ø¹ÙŠ Ø§Ù„Ù…Ù‚Ø±Ø± Ù„ØªØ¯Ø±ÙŠØ³ Ù…Ù‡Ø§Ø±Ø§Øª Ø§Ù„ÙƒØªØ§Ø¨Ø© Ø§Ù„ÙˆØ¸ÙŠÙÙŠØ© ÙÙŠ Ø§Ù„Ø¬Ø§Ù…Ø¹Ø§Øª Ø§Ù„Ø³Ø¹ÙˆØ¯ÙŠØ© - AlMugim, Tarig Muhammad (Ijaz Arabi Journal of Arabic Learning, 2021)
This study reveals the most prominent features of the development of university books related to teaching functional writing skills by comparing two books, the first "Al Tahrir Al Arabiy" by Ahmed Shawky Radwan and Al-Farih, which is considered a pioneer in its field. The second "Al Tahrir Al Kitabiy" by Hamdan Al-Zahrani and others. The second book considers educational standards in university book writing. One of the most important of these standards is to maintain the writing of educational goals before the start of each unit of study, providing feedback to students at the end of the unit from during the development of evaluation questions to the content of the article. It also pays attention to the aspects of applied skills required by students who are not proficient in Arabic and avoid deviations that may interfere with them, especially since the course is no longer than two hours, maintaining a modern model of these skills. The second book also adds new skills that were not in the previous book, such as writing meeting minutes, curriculum vitae, and other new writing skills in administrative and functional writing. This book also pays attention to the electronic aspect and links its contents to the World Wide Web. The second book is one of those books worth teaching in its field. There is also an urgent need to develop it to keep pace with the functional realities of the book and the formal changes that accompany many forms of writing, especially after being influenced by modern technical means and the emergence of other forms of writing. New for students to master it and apply it in the field of work. The researcher also reveals another trend in teaching functional writing skills that stems from the foundations of communication science and its modern applications